Critical potassium concentrations for the initial cultivation of Cedrela fissilis Vell - Nonato Junior Ribeiro dos Santos; José Zilton Lopes Santos; Sulianne Idalior Paião Rosado; Tainah Manuela Benlolo Brabosa; Mylena Rêgo Panza; Marcelo Tavares Nunes; Josinaldo Lopes Araújo Rocha (Revista Brasileira de Ciência do Solo)
ABSTRACT Providing nutrients in optimum quantities is essential for increasing the productivity of timber species. Despite this, we know little about the actual potassium (K) requirements of native Amazonian Forest species. This study aimed to determine the critical level of K deficiency and toxicity for the initial cultivation of cedar. We grew Cedrela fissilis seedlings in a nutrient solution under the effect of five concentrations of K (0, 1, 2, 5, and 8 mmol L-1) in a completely randomized design with five replications. After 30 days, we evaluated the relative growth rate, dry mass production, proline content, symptomatology, macro and micronutrient content and accumulation, and K absorption and utilization efficiencies. Concentrations of K positively influence the growth, accumulation, and content of nutrients in the dry mass of the aerial part of young cedar plants. Providing varying amounts of potassium significantly affects the nutritional and growth parameters of Cedrela fissilis seedlings. Potassium doses of 3.5 - 4.00 mmol L-1 in the growing substrate led to better nutritional status (26.08 - 27.28 g kg-1 of K) and plant growth.